A potent hepatitis B surface antigen response in subjects with inactive hepatitis B surface antigen carrier treated with pegylated‐interferon alpha - Cao, Zhenhuan; Liu, Yali; Ma, Lina; Lu, Junfeng; Jin, Yi; Ren, Shan; He, Zhimin; Shen, Chengli; Chen, Xinyue (Hepatology (Baltimore, Md.), 2017)
Hepatitis B surface antigen (HBsAg) clearance represents a clinical cure, although the clearance rate is extremely low. The aim of this study was to evaluate the feasibility and safety profiles of pegylated‐interferon α‐2a (PEG‐IFNα‐2a) as a therapeutic option for inactive HBsAg carriers. There were 144 inactive HBsAg carriers enrolled and divided into a therapeutic group (102 subjects) and a control group (42 subjects). PEG‐IFNα‐2a and PEG‐IFNα‐2a combined with adefovir dipivoxil were used for treatment group subjects with hepatitis B virus DNA <20 IU/mL and 20 IU/mL ≤ hepatitis B virus DNA < 2,000 IU/mL, respectively. Total therapy duration was no more than 96 weeks. HBsAg clearance and seroconversion rates at therapeutic weeks 48 and 96 were used to evaluate the therapeutic efficacy. Per protocol analysis showed that the HBsAg clearance rate and seroconversion rate in the treatment group were 29.8% and 20.2% at week 48 and increased to 44.7% and 38.3% at week 96, respectively. However, the HBsAg clearance rate in the control group was 2.4% at weeks 48 and 96, and no subject achieved seroconversion. The quantitative HBsAg levels and changes during the early period of treatment (at week 12 and week 24) as well as the alanine aminotransferase elevation at week 12 were strong predictors of HBsAg clearance. The adverse events were similar to those with treatment for chronic hepatitis B patients. Conclusion: High rates of HBsAg clearance and seroconversion could be achieved by PEG‐IFNα‐2a‐based treatments and the treatments were relatively safe for inactive HBsAg carriers. (Hepatology 2017;66:1058‐1066).